Regulatory controls for direct-to-consumer genetic tests: a case study on how the FDA exercised its authority. Issue 3 (3rd July 2017) - Curnutte, Margaret
Abstract : In February 2015, 23andMe received clearance from the United States Food and Drug Administration (FDA) for a carrier status test for a gene linked to Bloom syndrome. This was the first FDA authorization to market a direct-to-consumer (DTC) genetic test. Then, in April 2017, 23andMe obtained marketing clearance for an additional 10 tests that communicate information about individual disease risk. For roughly a decade it had been unclear whether FDA would regulate health-related DTC genetic tests. The recent approvals now provide an opportunity to examine how the Agency, in practice, has exercised its regulatory authority. This paper is the first case study to examine in detail how FDA has set standards for the marketing approval of DTC genetic tests.